Correction: Engineering of a chitin deacetylase to generate tailor-made chitosan polymers. - Martin Bonin; Antonia L Irion; Anika Jürß; Sergi Pascual; Stefan Cord-Landwehr; Antoni Planas; Bruno M Moerschbacher (PLoS Biology)
[This corrects the article DOI: 10.1371/journal.pbio.3002459.].